THE RELATION OF MALAYSIAN MALAY ISLAMIC CULTURE TO NATIONAL IDENTITY AND IDEOLOGY "PILLAR OF THE NATION" - Muhyidin, Muhyidin; Badruzaman, Irhas (Kodifikasia, 2024)
Islam and Malays in Malaysia are inseparable, having undergone a lengthy process of integration and leaving enduring legacies for Malaysia, the archipelago, and beyond. They collectively define the nation's identity, endorsed by the government. As a multicultural country, Malaysia affirms its adherence to Islam and the Malay heritage, with Malays playing a crucial role in maintaining political stability and preventing racial conflicts. Central to this harmony is the steadfast preservation of Malay culture by its people. Malay Islamic culture is preserved not only in the social life of society but also at the stage of constitutionally applicable legislation. The existing culture assimilates previous religions that have stopped and developed in Malay. Amid the onslaught of globalization which is being followed by all countries including Malaysia, Malay Muslim culture remains the characteristic of the Malaysian Malay nation. Malaysia as a democratic country has an ideology to be the basis for determining the direction of development steps. This paper is focused on finding compatibility between Malay Islamic culture preserved from generation to generation with the values of national identity contained in Malaysian legislation and the basic ideology of the state known as "Rukun Negara". It is a concept that binds the state with religious and ethnic entities to enhance the moral integrity of the nation. Keywords: Culture, Islam, Malay, National Policy, Malaysia,